Closure of Palatal Fistula with Tongue Flap - J.S. Bath; Gurpartap Singh; K.J.S. Mander (Indian Journal of Plastic Surgery)
Forty-five patients having large palatal fistulae (1.5-2cm) which could not be closed with local tissues were selected for this study. Forty-two patients out of this group were treated by anteriorly based tongue flap alone and in three patients a supplementary Burian flap was used. Complete closure of the fistula could be achieved in forty-three cases.